2011
DOI: 10.1051/0004-6361/201117017
|View full text |Cite
|
Sign up to set email alerts
|

Hot exozodiacal dust resolved around Vega with IOTA/IONIC

Abstract: Context. Although debris discs have been detected around a significant number of main-sequence stars, only a few of them are known to harbour hot dust in their inner part where terrestrial planets may have formed. Thanks to infrared interferometric observations, it is possible to obtain a direct measurement of these regions, which are of prime importance for preparing future exo-Earth characterisation missions. Aims. We resolve the exozodiacal dust disc around Vega with the help of infrared stellar interferome… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
79
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 61 publications
(90 citation statements)
references
References 56 publications
9
79
2
Order By: Relevance
“…Further scientifically significant data from interferometer on this object came with the longer baselines of PTI when Ciardi et al (2001) observed it and found puzzling signs of residuals in the K-band fits, consistent with a debris disk signal contaminating the stellar photospheric signal (as discussed in more detail in Barnes 2009;Lawler et al 2009;Akeson et al 2009). This finding was consistent with the further investigations with the CHARA Array and IOTA (Defrère et al 2011). These PTI and CHARA Array interferometric studies set the stage for two further, more detailed, studies of the star's photosphere itself.…”
Section: Vega (α Lyr)supporting
confidence: 87%
“…Further scientifically significant data from interferometer on this object came with the longer baselines of PTI when Ciardi et al (2001) observed it and found puzzling signs of residuals in the K-band fits, consistent with a debris disk signal contaminating the stellar photospheric signal (as discussed in more detail in Barnes 2009;Lawler et al 2009;Akeson et al 2009). This finding was consistent with the further investigations with the CHARA Array and IOTA (Defrère et al 2011). These PTI and CHARA Array interferometric studies set the stage for two further, more detailed, studies of the star's photosphere itself.…”
Section: Vega (α Lyr)supporting
confidence: 87%
“…This means that not only the cross-section, but also the mass is dominated by barely bound grains in the innermost parts of the disk. Interestingly, such steep size distributions are also invoked to explain NIR interferometric observations of hot exozodiacal dust (Defrère et al 2011;Mennesson et al 2013;Lebreton et al 2013). The drop in the size distribution from β ≈ 0.5 to β ≈ 1 is also much more pronounced in the inner disk than in the parent belt.…”
Section: Size Distributionmentioning
confidence: 85%
“…There are two additional problems with this scenario, which also serve as clues for solving the hot exozodiacal dust mystery. (1) Hot exozodiacal dust is thought to consist mostly of blowout grains with sizes around 0.01-0.1 µm (Akeson et al 2009;Defrère et al 2011;Mennesson et al 2013;Lebreton et al 2013), while P-R drag only transports bound grains to the sublimation zone, the smallest of which have sizes of about 1 µm. (2) The dust distribution resulting from the balance between P-R drag and collisions yields an SED with a positive slope in the infrared domain, while observations find negative slopes (e.g., Akeson et al 2009;Acke et al 2012), and the pile-up of dust is too inefficient to have an effect on the slope of the SED 15 .…”
Section: Other Explanations For Hot Exozodiacal Dustmentioning
confidence: 99%
See 2 more Smart Citations